The management of a stimulant abuse during pregnancy: a review of the literature published in Japan - Akazawa, Munetoshi; Hashimoto, Kazunori (Journal of Japan Society of Perinatal and Neonatal Medicine, 2020)
While a stimulant abuse is spreading widely in a society, a stimulant abuse during pregnancy has been reported even in Japan. In the previous domestic reports, many authors commented the management of the pregnant women with a stimulant abuse was difficult not only from the medical aspect but also from the social and legal aspect. To analyze the management of a stimulant abuse during pregnancy in Japan, using a Japanese national database, “Igaku Chuo Zasshi,” we reviewed the 13 cases of a stimulant abuse during pregnancy in Japan. Regarding the patients’ backgrounds, all the patients did not receive regular perinatal check-up. As severe maternal complications, intracranial bleeding and thyrotoxic crisis were reported. As neonatal complications, drug withdrawal syndrome was noticed in the four case. Two legal problems were discussed in the reports; whether the consent of the patients are needed for the urinary test and whether reporting to the police violates the concept of doctor-patient confidentiality? Since the case of a stimulant abuse during pregnancy is rare and containing the legal problems, the preparation of guideline for the management is needed.